2006
DOI: 10.1055/s-2006-941443
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Embolization

Abstract: Embolization is a remarkably versatile procedure used in nearly all vascular and nonvascular systems to treat a wide range of pathology. The published literature is rich with studies demonstrating the enormous therapeutic potential offered by embolization procedures, and the possibilities continue to expand with the advent of new embolization agents and techniques. Unfortunately, with this variety and innovation comes a wide spectrum of potential complications, not always easy to classify and summarize, associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 145 publications
0
63
0
Order By: Relevance
“…Unenhanced MDCT is most likely insufficient in cases of large hematoma when only MDCTA would show active bleeding and warn the clinicians [18,23,[32][33][34][35]. Of course, a positive finding on MDCTA can help in localizing the bleeding site [7,[38][39][40][41][42][43]. In cases of renal dysfunction, our study does not reveal whether the clinical benefit is high enough to offset the potential complications of iodinated contrast material.…”
Section: Embolization For Soft-tissue Hemorrhagementioning
confidence: 81%
“…Unenhanced MDCT is most likely insufficient in cases of large hematoma when only MDCTA would show active bleeding and warn the clinicians [18,23,[32][33][34][35]. Of course, a positive finding on MDCTA can help in localizing the bleeding site [7,[38][39][40][41][42][43]. In cases of renal dysfunction, our study does not reveal whether the clinical benefit is high enough to offset the potential complications of iodinated contrast material.…”
Section: Embolization For Soft-tissue Hemorrhagementioning
confidence: 81%
“…Few cases of elective occlusion of larger vessels with a variety of devices have also been described (9,10). Embolization procedure may involve risk of device migration, non-target embolization, lung infarction and recanalization (11). Occlusion of APCs in Fontan patients is associated with improved clinical outcome (12).…”
Section: Discussionmentioning
confidence: 99%
“…Sakamoto et al [45] indicated a concern for a RIPA-pulmonary vasculature shunt contributing to the migration of Lipiodol or chemotherapeutic agent to the lung tissue causing ALI during TACE. This concern has been similarly shared by Bilbao et al [46] and Clark [27] . Hatamaru et al [47] reported a fatal pulmonary complication associated with TACE for HCC involving the RIPA, which was shown angiographically to contain an AV shunt.…”
Section: Introductionmentioning
confidence: 52%